Результати польових досліджень дискаторів в різних грунтових умовах - Теслюк, Г. В.; Волик, Б. А.; Пугач, А. М.; Брижатий, І. Ю.; Teslyuk, G.; Volyk, B.; Pugach, А.; Brygatiy, I. (КНТУ, 2016)
В роботі наведені результати досліджень роботи дискаторів в умовах рядової експлуатації на грунтах із різним питомим зчепленням часток, який прийнятий за інтегральний показник механіко- технологічних властивостей грунту. За основу були взяті близькі за конструктивним виконанням машини серійного виробництва. The article presents results of studying the work dictators under conditions of ordinary use on soils with different cohesion of the particles, which prineto us as the integral manifold of index the entire group of mechanical-technological properties of the soil. As a quality indicator of chopping used the coefficient of structure, defined as the ratio of the mass of agronomically valuable aggregates to the total mass of soil sampling. Additionally, the results of development of methods for the assessment of quality crushing and ploughing of crop residues. Research needs connected with the necessity of obtaining objective data on the disk of the working bodies, composed of combined units of various designs.
The results of field studies of disc harrows in various soil conditions
Keywords: дискатор; питоме зчеплення часток грунту; якість кришення; disk harrow; specific adhesion of soil particles; the quality of crushing